Comparison between crown thinning and girdling to enhance sporadic tree species in a coppice stand in Central Italy - Riccardo Paoloni; Alessandra Pacini; Claudio Bidini; Luca Marchino; Maria Chiara Manetti; Alessandro Ceppatelli; Francesco Pelleri (Annals of Silvicultural Research)
Sporadic valuable tree species and especially Sorbus species have gained importance in forest management as they increase tree biodiversity, ensure a higher resilience of the stand to climate change, and enhance valuable timber production. This paper reports the first results of a trial carried out in Central Italy in a Turkey oak coppice stand (aged 17 years) where three different silvicultural treatments (crown thinning, girdling and unthinned control) were applied to favour sporadic tree species. The monitoring was carried out for 5 years and showed the limits of girdling application as Mediterranean species like Turkey oak form easily scar cords and epicormic sprouting. Furthermore, the progressive reduction of canopy cover of the competitors resulted from girdling and the effect of the thinning and girdling on the growth of selected service trees (Sorbus domestica L.) were evaluated. The first results of this research have pointed out some difficulties in the girdling application and a higher effect of crown thinning in stimulating the growth of selected service trees.